Appropriate Role and Status of Small Industries in Village Development - Riahi, Saiid Mir (International Journal of Bio-resource and Stress Management, 2010)
Development in its modern version has got a common definition in the societies facilitated by industrial growth and mechanization. The load on society has considerably took place within a short period of time. The emphasis is on the villages and cities development along with each other by establishing small industries and localizing them in the villages. To keep and develop villages, rural development is defined as: to speed up village’s development and to pay deep attention to the improvement of rural livelihood and their environment, to provide occupation fields and to increase rural income, to encourage and support investment and to develop activities. One of the most important principles of social welfare is to adjust the urban and rural incomes. So creating the job chances in villages helps not only the increase of incomes but also it decrease of emigration to the cities and protect the environment. Creating the new job chances means to take preference to small industries in the villages. And this will be possible by entrance and appearance of small industries at first stage. In this essay, the most important perspectives about development index and the significance of small rural industries are discussed and at the end are concluded.